2022
DOI: 10.1111/1748-8583.12432
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive human resource management in freelancers' employment relationships: The role of organizational needs and freelancers' psychological contracts

Abstract: This study aimed to advance our understanding of inclusive human resource management (HRM) in freelance employment. We examined organizational needs and freelancers' psychological contracts with a qualitative interview study among eight dyads of HR managers and freelancers. Although the findings showed that organisations and freelancers have different interests, both parties agreed on what inclusive HRM entails in freelancers' employment relationships. However, within the dyads, the content of the psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The evolution of this gig economy, and increased reliance on temporary workers, is also resulting in a more flexible yet fragmented workforce (Van den Groendaal et al, 2023). Studies have shown that the rise of gig work can reduce social cohesion (Braganza et al, 2022) and destabilise employee trust and commitment to organisations (Van den Groenendaal et al, 2023). Therefore, one of the perils of a task-focused work system is the impact on social connectedness and the resultant feelings of organisational belonging.…”
Section: Task-focused Work Systemsmentioning
confidence: 99%
“…The evolution of this gig economy, and increased reliance on temporary workers, is also resulting in a more flexible yet fragmented workforce (Van den Groendaal et al, 2023). Studies have shown that the rise of gig work can reduce social cohesion (Braganza et al, 2022) and destabilise employee trust and commitment to organisations (Van den Groenendaal et al, 2023). Therefore, one of the perils of a task-focused work system is the impact on social connectedness and the resultant feelings of organisational belonging.…”
Section: Task-focused Work Systemsmentioning
confidence: 99%
“…In addition, IHRM advocates the application of fexible work systems such as shift changes, rotations, and leave transfers in the task allocation process and gives nurses a sense of autonomy through empowerment practices [13]. Job fexibility and autonomy provided by personalized confguration allow nurses to proactively engage in innovative behavior such as creative problem solving to realize resource augmentation [37]. Finally, one's commitment to risky creative activities requires the necessary incentives and support, and favorable compensation and benefts can efectively hedge the risk of loss associated with innovation [26].…”
Section: Ihrm and Nurses' Innovativementioning
confidence: 99%
“…Perceived organizational status, as defined in the field of organizational behavior research, refers to an individual’s self-evaluation of their value and status within an organization [ 48 ]. This perception significantly affects the attitudes and behaviors of employees [ 55 ]. Studies indicate that employees with a high perceived organizational status tend to be more committed to their organization and feel a greater sense of responsibility to contribute towards achieving its goals and mission [ 56 ].…”
Section: Theoretical Foundation and Research Hypothesesmentioning
confidence: 99%